#Fake news: a systematic review of mechanical thrombectomy results among neurointerventional stroke surgeons on Twitter. (15th September 2018) - Dmytriw, Adam Andrew; Sorenson, Thomas Joseph; Morris, Jonathan M; Nicholson, Patrick J; Hilditch, Christopher Alan; Graffeo, Christopher S; Brinjikji, Waleed
Abstract : Objective: Twitter is a popular social media platform among physicians. Neurointerventionalists frequently document their lifesaving mechanical thrombectomy cases on Twitter with very favorable results. We fear that there may be some social media publication bias to tweeted mechanical thrombectomy cases with neurointerventionalists being more likely to tweet cases with favorable outcomes. We used these publicly documented cases to analyze post-intervention Twitter-reported outcomes and compared these outcomes with the data provided in the gold standard literature. Methods: Two reviewers performed a search of Twitter for tweeted cases of acute ischemic strokes treated with mechanical thrombectomy. Data were abstracted from each tweet regarding baseline characteristics and outcomes. Twitter-reported outcomes were compared with the Highly Effective Reperfusion Evaluated in Multiple Endovascular Stroke (HERMES) trial individual patient meta-analysis. Results: When comparing the tweeted results to HERMES, tweeted cases had a higher post-intervention rate of modified Thrombolysis In Cerebral Infarction (mTICI) scale score of 2c/3 (94% vs 71%, respectively; p<0.0001) and rate of National Institutes of Health Stroke Scale (NIHSS) score ≤2 (81% vs 21%, respectively; p<0.0001). There were no reported complications; thus, tweeted cases also had significantly lower rates of complications, including symptomatic intracerebral hemorrhage (0% vs 4.4%, respectively; p<0.0001), type 2 parenchymal hemorrhage (0% vs 5.1%, respectively; p<0.0001), and mortality (0% vs 15.3%, respectively; p<0.0001). Conclusions: There is a significant difference between social media and reality even within the 'MedTwitter' sphere, which is likely due to a strong publication bias in Twitter-reported cases. Content on 'MedTwitter', as with most social media, should be accepted cautiously.